2011
DOI: 10.1093/ageing/afr027
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality-of-life in older people in care homes

Abstract: to fully understand residents' QoL, detailed interview-based instruments, administered by an experienced interviewer are needed. To measure current QoL, for example, as an outcome measure, a simple single rating scale may suffice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…However, they tried to accept and adapt to life in an NH. These findings are largely consistent with previously published research (Bradshaw, Playford, & Riazi, ; Chang, ; Hall, Opio, Dodd, & Higginson, ; Hjaltadottir & Gustafsdottir, ; Kwong, Lai, & Liu, ; Murphy, Cooney, & Casey, ; Robichaud, Durand, Bedard, & Ouellet, ; Schenk, Meyer, Behr, Kuhlmey, & Holzhausen, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, they tried to accept and adapt to life in an NH. These findings are largely consistent with previously published research (Bradshaw, Playford, & Riazi, ; Chang, ; Hall, Opio, Dodd, & Higginson, ; Hjaltadottir & Gustafsdottir, ; Kwong, Lai, & Liu, ; Murphy, Cooney, & Casey, ; Robichaud, Durand, Bedard, & Ouellet, ; Schenk, Meyer, Behr, Kuhlmey, & Holzhausen, ).…”
Section: Discussionsupporting
confidence: 92%
“…Hall et al. () and Schenk et al. () identified health status as one of the key dimensions of residents' QOL.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a need to further explore factors and activities that can influence well-being in nursing homes and how prevalent these are in nursing homes to date. Everyday activities have in previous studies been described by nursing home residents as important for their QoL across contexts and countries (Cooney et al 2009, Hall et al 2011, Schenk et al 2013. Engagement in social activities have been described as essential to the health and well-being of residents (Bergman-Evans 2004, Drageset 2004) and residents themselves have narrated that they primarily engage in activities to be socially connected (Thomas et al 2013, Tak et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement in everyday activities is recognized as positively influencing the quality of life (QoL) of residents in nursing homes internationally (Cooney et al 2009, Hall et al 2011, Schenk et al 2013. However, studies across countries have shown that the amount of activities offered in nursing homes is limited (Kjøs & Havig 2016) and that residents often are inactive and lonely (Harper Ice 2002, Slettebø 2008, den Ouden et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…12 Difficulties in the administration and interpretation of outcome measures have been reported. [43][44][45] These issues present particular challenges for designing studies and powering trials and respondent burden.…”
Section: Discussionmentioning
confidence: 99%